APPROACHES OF EU COUNTRIES TO SOLVING ENVIRONMENTAL AND ECONOMIC PROBLEMS IN THE CONTEXT OF CIRCULAR ECONOMY DEVELOPMENT (INNOVATIVE ECONOMY, 2023)
Shyshpanova N.O. APPROACHES OF EU COUNTRIES TO SOLVING ENVIRONMENTAL AND ECONOMIC PROBLEMS IN THE CONTEXT OF CIRCULAR ECONOMY DEVELOPMENTPurpose. Analysis of the EU country's experience in the implementation of approaches to solving ecological and economic problems in the context of the development of the circular economy, which will allow to determine the priority directions for the economic development of Ukraine, to form an integrated system of state organizational and economic support for the implementation of the circular economy model.Methodology of the research. To achieve the goal, the following research methods were used: theoretical synthesis, analysis, abstract-logical - to reveal the essence of the concept of "circular economy", justify the research methodology and determine theoretical generalizations; monographic and comparative - for the systematization of scientific approaches of scientists to the theoretical aspects of the development of the circular economy and the expansion of the methodological base; graphic - for visualization of research results.Findings. The article presents the results of research into the theoretical aspects of the circular economy as a new paradigm for solving environmental and economic problems in the modern globalized world. The main principles of the circular economy concept and the advantages of its implementation are highlighted based on the experience of the European Union, a global leader in this field. The main goals, priorities and measures of the EU in the implementation of the circular economy are disclosed. Examples of successful use of circular economy business models in EU countries are given.It is substantiated that the transition to a circular economy should be systemic, deep and transformational. This will require the agreement and cooperation of all stakeholders at all levels – EU, national, regional and local and international. Ukrainian business, adopting the experience of managing circular business models in the EU countries, should make the transition to sustainable development, namely to rational production and responsible consumption.Originality. The justification of the expediency of using the experience of the EU countries in the implementation of approaches to solving ecological and economic problems in the context of the development of the circular economy was further developed.Practical value. Proposals substantiated by research results can be used by authorities and business structures for the introduction and management of circular business models.Key words: circular economy, environmental problems, environmental protection, experience of EU countries, waste.
Keywords: circular economy; environmental problems; environmental protection; experience of EU countries; waste